Inducing mutations in the mouse genome with the chemical mutagen ethylnitrosourea - S.M.G. Massironi (Brazilian Journal of Medical and Biological Research, 2006)
When compared to other model organisms whose genome is sequenced, the number of mutations identified in the mouse appears extremely reduced and this situation seriously hampers our understanding of mammalian gene function(s). Another important consequence of this shortage is that a majority of human genetic diseases still await an animal model. To improve the situation, two strategies are currently used: the first makes use of embryonic stem cells, in which one can induce knockout mutations almost at will; the second consists of a genome-wide random chemical mutagenesis, followed by screening for mutant phenotypes and subsequent identification of the genetic alteration(s). Several projects are now in progress making use of one or the other of these strategies. Here, we report an original effort where we mutagenized BALB/c males, with the mutagen ethylnitrosourea. Offspring of these males were screened for dominant mutations and a three-generation breeding protocol was set to recover recessive mutations. Eleven mutations were identified (one dominant and ten recessives). Three of these mutations are new alleles (Otop1mlh, Foxn1sepe and probably rodador) at loci where mutations have already been reported, while 4 are new and original alleles (carc, eqlb, frqz, and Sacc). This result indicates that the mouse genome, as expected, is far from being saturated with mutations. More mutations would certainly be discovered using more sophisticated phenotyping protocols. Seven of the 11 new mutant alleles induced in our experiment have been localized on the genetic map as a first step towards positional cloning.